Comparison of the Effects of Indonesian Healthy Gymnastics on Cardiovascular Endurance among Upper-Grade and Lower-Grade Elementary School Students in Urban and Rural Areas - Lia Daniel; Fajri Hamzah; Suaib Nur; Imam Pribadi; Agus Ismail (ASHA Publishing, 2026)
This study aimed to compare the effects of Indonesian Healthy Gymnastics on cardiovascular endurance among upper-grade and lower-grade elementary school students in urban and rural areas. A quantitative approach with a two-group pretest-posttest design was employed. The participants consisted of 48 elementary school students selected purposively from SDN 10 Buntu Pepasan and SDN 7 Buntu Pepasan, North Toraja Regency, South Sulawesi, Indonesia. Cardiovascular endurance was measured using the 6-Minute Run Test for lower-grade students and the 12-Minute Run Test for upper-grade students. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s test, the Wilcoxon Signed Rank Test, and the Mann-Whitney U test. The results indicated a significant improvement in cardiovascular endurance after participation in Indonesian Healthy Gymnastics, as evidenced by the increase in mean scores from 1025.4 in the pretest to 1562.7 in the posttest (p < 0.05). Significant differences were also observed between students from urban and rural areas (p = 0.032) and between upper-grade and lower-grade students (p = 0.015). Although urban students demonstrated higher absolute gain scores, rural students exhibited greater percentage improvements (19.15%) compared with urban students (16.35%). Furthermore, upper-grade students achieved better cardiovascular endurance than lower-grade students, reflecting differences in physiological development and exercise adaptation. These findings suggest that Indonesian Healthy Gymnastics is an effective school-based aerobic exercise program for improving cardiovascular endurance among elementary school students. The study also emphasizes the necessity of considering developmental characteristics and environmental contexts when designing physical education programs. Consequently, age-appropriate and context-sensitive physical activity interventions are recommended to optimize children's health and physical fitness outcomes.